Mycosporine-Like Amino Acids (MAAs) in Zooplankton - Samuel Hylander (Marine Drugs, 2020)
Organisms have different adaptations to avoid damage from ultraviolet radiation and one such adaptation is the accumulation of mycosporine-like amino acids (MAAs). These compounds are common in aquatic taxa but a comprehensive review is lacking on their distribution and function in zooplankton. This paper shows that zooplankton MAA concentrations range from non-detectable to ~13 µg mgDW−1. Copepods, rotifers, and krill display a large range of concentrations, whereas cladocerans generally do not contain MAAs. The proposed mechanisms to gain MAAs are via ingestion of MAA-rich food or via symbiotic bacteria providing zooplankton with MAAs. Exposure to UV-radiation increases the concentrations in zooplankton both via increasing MAA concentrations in the phytoplankton food and due to active accumulation. Concentrations are generally low during winter and higher in summer and females seem to deposit MAAs in their eggs. The concentrations of MAAs in zooplankton tend to increase with altitude but only up to a certain altitude suggesting some limitation for the uptake. Shallow and UV-transparent systems tend to have copepods with higher concentrations of MAAs but this has only been shown in a few species. A high MAA concentration has also been shown to lead to lower UV-induced mortality and an overall increased fitness. While there is a lot of information on MAAs in zooplankton we still lack understanding of the potential costs and constraints for accumulation. There is also scarce information in some taxa such as rotifers as well as from systems in tropical, sub(polar) areas as well as in marine systems in general.